2008
DOI: 10.1016/j.matbio.2008.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Modification and functional inactivation of the tropoelastin carboxy-terminal domain in cross-linked elastin

Abstract: The carboxyl terminus of tropoelastin is a highly conserved, atypical region of the molecule with sequences that define both cell and matrix interactions. This domain also plays a critical but unknown role in the assembly and crosslinking of tropoelastin during elastic fiber maturation. Using a competitive ELISA with an antibody to an elastase-resistant epitope in the carboxy-terminus of tropoelastin (domain-36), we quantified levels of the domain-36 sequence in elastase-derived peptides from mature, insoluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…However, the strong sequence conservation in this exon of tropoelastin genes is consistent with several reports of an important role for the C-terminal domain in interactions with other proteins and cells to contribute to the assembly and final architecture of the extracellular matrix in vivo (Broekelmann et al, , 2008Brown-Augsburger et al, 1994, 1996Hinek and Rabinovitch, 1993;Hsiao et al, 1999;Rodgers and Weiss, 2004). This view is also supported by several reports of human tropoelastin mutations affecting this C-terminal domain.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, the strong sequence conservation in this exon of tropoelastin genes is consistent with several reports of an important role for the C-terminal domain in interactions with other proteins and cells to contribute to the assembly and final architecture of the extracellular matrix in vivo (Broekelmann et al, , 2008Brown-Augsburger et al, 1994, 1996Hinek and Rabinovitch, 1993;Hsiao et al, 1999;Rodgers and Weiss, 2004). This view is also supported by several reports of human tropoelastin mutations affecting this C-terminal domain.…”
Section: Introductionsupporting
confidence: 86%
“…In the penultimate exon, the conserved final two amino acids are in bold and the crosslinking motif normally positioned near the N-terminal of the exon is underlined. matrix, at least in mammalian tissues (Broekelmann et al, , 2008Brown-Augsburger et al, 1994, 1996Hinek and Rabinovitch, 1993;Hsiao et al, 1999;Rodgers and Weiss, 2004), might initially suggest that this second elastin gene represents an actual or incipient pseudogene which is either not expressed or results in a protein product which cannot be incorporated into elastic tissues.…”
Section: Figmentioning
confidence: 99%
“…Others have shown that the C terminus of tropoelastin may be lost in mature elastic fibers, which would account for the lack of cell interaction to soluble bovine elastin (37).…”
Section: Discussionmentioning
confidence: 99%
“…These soluble forms of elastin have shown properties similar to the native tropoelastin, such as ability to coacervate as well as alteration of cell signaling via elastin receptors. However, animal-derived elastin is a heterogeneous partially crosslinked mixture of peptides with inadequate cell binding sites [40]. Elastin derivatives can also be produced via peptide synthesis to generate ELPs, or biosynthetically to form recombinant proteins.…”
Section: Production Of Elastin-sequence Derived Materialsmentioning
confidence: 99%